Analysis of disturbances in the high-latitude ionosphere during a multi-step magnetic storm on November 4-5, 2023 based on incoherent scattering radar data - Chernogor, L.F.; Tkachenko, M. Yu. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 2025)
Relevance. The ionosphere is a key radio channel for radio communications, navigation, radiolocation, remote sensing and radio astronomy. Its condition determines the quality of operation of ground and space technological systems. The most powerful disturbances in the parameters of the ionosphere are caused by solar storms. As a result, radio communications, radar and radio sounding of near-Earth and deep space may be disrupted or made impossible. The high-latitude ionosphere (above ±60°) is most sensitive to such influences, where magnetospheric convection, current amplification, Joule heating, and energetic particle precipitation simultaneously manifest themselves. Incoherent scattering radar makes it possible to study the temporal and spatial dynamics of key ionosphere parameters — electron and ion temperatures, electron concentration, plasma velocities, and ionic composition. Since changes in the state of the ionospheric channel can cause failures or make it impossible to conduct a radio communication session, the operation of radio navigation devices, and positioning using satellite navigation systems, a comprehensive study of such disturbances is relevant.The aim of this work is to study the features of disturbances in the high-latitude ionosphere using incoherent scattering radar.Methods and Methodology. According to measurements from the Poker Flat incoherent scattering radar (Alaska, USA) during a multi-step magnetic storm on November 4–5, 2023, a study was conducted and the parameters of high-latitude ionospheric disturbances in the Northern Hemisphere were established.Results. It was found that the largest disturbances were observed on the night of November 4–5  and in the second half of November 5 and were accompanied by extreme values ​​of Ti up to (5–6)·10³ K, high velocities of E×B drift (>500 m/s), local disturbances of Te and a drop in O⁺/N₂. The effects of a qualitative change in the chemical composition of the ionospheric plasma and thermosphere (a change in the distribution of the O⁺/N₂ ratio values ​​over height and a level height of about 0.5) played a key role in the formation of the negative phase of the ionospheric storm, especially on November 5–6, when Ne remained low at elevated temperatures and the preservation of convection. Recovery from these disturbances took at least two days: first, the electron concentration recovered (22:00 on November 6 - 8:00 on November 8), then the electron and ion temperatures and plasma drift velocities returned to background values, while enhanced convective processes at altitudes above 360 ​​km persisted until the end of the observation period.